Tissue-Related Hypoxia Attenuates Proinflammatory Effects of Allogeneic PBMCs on Adipose-Derived Stromal Cells In Vitro - Polina I. Bobyleva; Elena R. Andreeva; Aleksandra N. Gornostaeva; Ludmila B. Buravkova (Stem Cells International)
Human adipose tissue-stromal derived cells (ASCs) are considered a perspective tool for regenerative medicine. Depending on the application mode ASC/allogeneic immune cell interaction can occur in the systemic circulation under plenty high concentrations of O2 and in target tissues at lower O2 levels. Here we examined the effects of allogeneic PHA-stimulated peripheral blood mononuclear cells (PBMCs) on ASCs under ambient (20%) oxygen and “physiological” hypoxia (5% O2). As revealed with microarray analysis ASCs under 20% O2 were more affected by activated PBMCs, which was manifested in differential expression of more than 300 genes, whereas under 5% O2 only 140 genes were changed. Altered gene pattern was only partly overlapped at different O2 conditions. Under O2 ASCs retained their proliferative and differentiative capacities, mesenchymal phenotype, and intracellular organelle’ state. ASCs were proinflammatory activated on transcription level that was confirmed by their ability to suppress activation and proliferation of mitogen-stimulated PBMCs. ASC/PBMCs interaction resulted in anti-inflammatory shift of paracrine mediators in conditioning medium with significant increase of immunosuppressive LIF level. Our data indicated that under both ambient and tissue-related O2 ASCs possessed immunosuppressive potential and maintained functional activity. Under “physiological” hypoxia ASCs were less susceptible to “priming” by allogeneic mitogen-activated PBMCs.